Continuous Exercise but Not High Intensity Interval Training Improves Fat Distribution in Overweight Adults - Shelley E. Keating; Elizabeth A. Machan; Helen T. O'Connor; James A. Gerofi; Amanda Sainsbury; Ian D. Caterson; Nathan A. Johnson (Journal of Obesity)
Objective. The purpose of this study was to assess the effect of high intensity interval training (HIIT) versus continuous aerobic exercise training (CONT) or placebo (PLA) on body composition by randomized controlled design. Methods. Work capacity and body composition (dual-energy X-ray absorptiometry) were measured before and after 12 weeks of intervention in 38 previously inactive overweight adults. Results. There was a significant group × time interaction for change in work capacity (P<0.001), which increased significantly in CONT (23.8±3.0%) and HIIT (22.3±3.5%) but not PLA (3.1±5.0%). There was a near-significant main effect for percentage trunk fat, with trunk fat reducing in CONT by 3.1±1.6% and in PLA by 1.1±0.4%, but not in HIIT (increase of 0.7±1.0%) (P=0.07). There was a significant reduction in android fat percentage in CONT (2.7±1.3%) and PLA (1.4±0.8%) but not HIIT (increase of 0.8±0.7%) (P=0.04). Conclusion. These data suggest that HIIT may be advocated as a time-efficient strategy for eliciting comparable fitness benefits to traditional continuous exercise in inactive, overweight adults. However, in this population HIIT does not confer the same benefit to body fat levels as continuous exercise training.